TEACHERS' PROFESSIONAL DEVELOPMENT AND TEACHERS' TEACHING PRACTICE - Nida Fauziah, - (2018)
The increased demand for high-quality education requires teachers to update and improve their teaching performance. This teaching performance covers teachers' language proficiency, teachers' content knowledge, and teachers' teaching skill. Thus, it is urgent for teachers to continuously develop themselves through professional development. This present study investigates activities undertaken by teachers to support their professional development within the period of 2015-2017 and advantages of professional development activities on their teaching practice. Two English teachers at a junior high school served as respondents. Teacher 1 was a senior one with more than 25 years of teaching experiences. On the other hand, even though Teacher 2 has taught more or less 15 years, but in that school she was a relatively new teacher. She has taught for about 5 years. Through class observations, questionnaires and interviews, it was revealed that Teacher 1 participated in workshops, attended teacher association meeting, conducted action research, pursued further studies, and became an English coach. Teacher 2 participated in workshops and attended teacher association meeting. To some extent, professional development activities have helped teachers to enrich their English vocabulary, formulate questions, use English expressions in different situations, design various learning activities as well as assess students through different approaches. However, the professional development activities have not given significant impacts on respondents' teaching performance. For example, although the respondents admitted that their language proficiency improved, but the aspects of the improvement were only in getting new vocabulary, new English expressions, and formulating questions. It showed that professional development activities only touched upon superficial matters. Moreover, the activities did not address teachers' needs in the real teaching-learning situations. The respondents found that some professional development activities such as workshops and teacher association tended to raise similar topics from time to time. Besides, the invited tutors from the teacher association often discussed the topics at the theoretical levels. They seemed to have lack understanding of the real problems enountered by teachers. Consequently, there were some discrepancies between what was delivered by the tutors and what was needed by the teachers. It made professional development activities look like routines. Therefore, it is suggested that professional development activities should be well-planned and continuously evaluated